Paranoid visions : Spies, conspiracies and the secret state in British television drama - Oldham, Joseph (Joseph Christopher) (Book collections on Project MUSE., 2017)
Paranoid Visions explores the history of the spy and conspiracy genres on British television, from 1960s Cold War series through 1980s paranoid conspiracy dramas to contemporary 'war on terror' thrillers. It analyses classic dramas including Tinker Tailor Soldier Spy, Edge of Darkness, A Very British Coup, and Spooks. This book will be an invaluable resource for television scholars interested in a new perspective on the history of television drama and intelligence scholars seeking an analysis of the popular representation of espionage with a strong political focus, as well as fans of cult British television and general readers interested in British cultural history.